2021
DOI: 10.2147/ppa.s298594
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Its Associated Factors Among Adult HIV-Infected Patients on Antiretroviral Therapy in South Western Ethiopia, 2020

Abstract: Background Good adherence to antiretroviral therapy (ART) suppresses the viral load, reconstitutes the immune system, and decreases opportunistic infections among HIV-positive patients. However, adherence to ART is still challenging in developing countries such as Ethiopia. The study, therefore, aimed to assess adherence and its associated factors among HIV-positive patients on ART in southern Ethiopia in 2020. Materials and Methods A cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In our study, being diagnosed at WHO stages II and III was independently associated with lower chances of ART adherence. This is consistent with studies by Angelo et al (2021), and Negash et al (2013), who also reported that WHO stages II and III were significantly associated with lower chances of adherence than in those with WHO clinical stage I [ 23 , 24 ]. This may be due to stigma and discrimination at advanced stages of HIV infection associated with overt manifestation of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, being diagnosed at WHO stages II and III was independently associated with lower chances of ART adherence. This is consistent with studies by Angelo et al (2021), and Negash et al (2013), who also reported that WHO stages II and III were significantly associated with lower chances of adherence than in those with WHO clinical stage I [ 23 , 24 ]. This may be due to stigma and discrimination at advanced stages of HIV infection associated with overt manifestation of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The level of poor adherence to ART therapy was significantly affected by the age of the patients, where patients in the age group of ≤24 years were more likely to be non-adherent to ART treatment. This is similar to studies conducted in Ethiopia 36 , 37 that had found an increased level of adherence as age goes beyond 25 years. During the time of COVID-19, the young population may not visit health institutions due to fear of discrimination and stigma.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, poor educational status among rural residents might hinder their adherence to PMTCT. 46 The odds of adherence were 2.24 times higher among women who received partner support as compared to those women who had not. This finding is congruent with findings of previous studies, 47,48 and could be attributed to improved psychological and economic accessibility by accompanying women to PMTCT clinics.…”
Section: Discussionmentioning
confidence: 95%
“…A likely explanation is that women from rural areas might have limited access to PMTCT services and information. Besides, poor educational status among rural residents might hinder their adherence to PMTCT 46 …”
Section: Discussionmentioning
confidence: 99%